Minions : the rise of Gru [videorecording (DVD)] (Universal, 2022)
In the heart of the 1970s, amid a flurry of feathered hair and flared jeans, Gru (Oscar nominee Steve Carell) is growing up in the suburbs. A fanboy of a supervillain supergroup known as the Vicious 6, Gru hatches a plan to become evil enough to join them. Luckily, he gets some mayhem-making backup from his loyal followers, the Minions. Together, Kevin, Stuart, Bob, and Otto, a new Minion sporting braces and a desperate need to please, deploy their skills as they and Gru build their first lair, experiment with their first weapons and pull off their first missions.